Swelling and thermal effects on mechanical properties of NR/EPDM filled graphene nanoplatelets for engine mounting - Karim, Khairu Ilwani (2021)
Nowadays, rubber blend nanocomposites have fascinated most researchers to be utilized in engine mounting. Graphene nanoplatelets (GNPs) have been known to have outstanding properties in physical, mechanical, electrical and thermal. In some applications, structures and components may be subjected to harsh service conditions such as high heat, liquid and dynamic stress. This research is aimed to explore the swelling and thermal effects on the physical and mechanical properties of NR/EPDM filled graphene nanoplatelets (GNPs) for engine mounting. In Stage 1, the effect of the thermal cycle on the tensile properties of NR/EPDM blends and NR/EPDM nanocomposites were studied. The NR/EPDM blends and NR/EPDM nanocomposites were prepared through melt compounding. Then, both materials were subjected to a thermal cycle before their tensile properties were measured. In Stage 2, both NR/EPDM blends and NR/EPDM nanocomposites were subjected to oil immersion in three types of oil medium; brake oil, gear oil and engine oil to assess their effects on the tensile properties. In Stage 3, the oil-immersed composites were subjected to dynamic loading to determine the fatigue life cycles due to more critical tensile properties under swelling media. Finally, the findings were further supported by swelling behaviour and compositional (FTIR), structural (XRD), thermal (DMTA) and morphological characteristics (SEM). Thermally affected NR/EPDM nanocomposites showed higher performance under tensile stress at the thermal cycles of 60°C and 120°C if compared to NR/EPDM blend. The tensile strength and modulus of elongation at 100% and 300% for nanocomposites were consistently 30-60% higher than NR/EPDM blend due to reinforcing effects of GNPs and their good interaction with the matrix which supported by the higher crosslink density in NR/EPDM nanocomposites. The declination in tensile properties with the increased thermal cycle was due to the chain embrittlement effect and in line with the increase in amorphous phases showing by the broadening of XRD spectra. Furthermore, the NR/EPDM nanocomposites exhibited better performance under the effect of swelling media in comparison with NR/EPDM blends. The immersion in gear and engine oil caused a major deterioration to both materials and caused sudden drops in tensile properties. The increment in elongation at break once immersed in oils was due to the softening effect of the rubber chains and re-distribution of GNPs sheets observed in XRD and FTIR analyses. The morphological analysis also verified that the swelling process caused the formation of wrinkles and cracking on both rubber surfaces, which appears to reduce in NR/EPDM nanocomposites. The swollen NR/EPDM blend and nanocomposites were further tested under fatigue stress. The unswollen and swollen nanocomposites exhibited higher resistance towards dynamic stress with maximum fatigue life higher than the blends about 105 cycles. The morphological analysis illustrates a more wrenching pattern on the fatigue fracture of the NR/EPDM nanocomposites. This has proven that the NR/EPDM nanocomposites can withstand thermal cycles, oils and fluctuating stress better than NR/EPDM blend and showed higher potential to be utilized as engine mounting material.